Endoscopic Management of Postlaparoscopic Sleeve Gastrectomy Leaks: A Single-Center Experience - Jagtap, Nitin; Yashavanth, H.S.; Kalapala, Rakesh; Katakwar, Abhishek; Ramchandani, Mohan; Ajmere, Vaibhav; Tandan, Manu; Darishetty, Santosh; Rao, G. Venkat; Reddy, D. Nageshwar (Journal of Digestive Endoscopy, 2020)
Introduction Laparoscopic sleeve gastrectomy (LSG) is a commonly performed bariatric surgery. Sleeve leak is the most important complication, with an incidence of 1.9 to 2.4%. Various endoscopic approaches to LSG have been used, including self-expanding metal stents (SEMSs), glue injection, and clipping along with percutaneous drainage. This study was aimed to study the role of endotherapy in the management of post-LSG leaks.Methods This study included patients referred for endotherapy for post-LSG leak between January 2016 and December 2018. We maintained data prospectively, which included the location and type of leak, type of endotherapy, adverse events, and time for leak closure. Primary endotherapy included mega SEMS placement; if it failed, then secondary endoscopic therapy was performed.Results Seven patients (four females, with a mean age of 45.2 years) with a preoperative body mass index of mean 38.5 kg/m2 underwent endotherapy for post-LSG leaks. Two were acute, four were early, and the remaining one was late leak. Five were located proximally near gastroesophageal junction and two at the midsleeve level. In four (57.1%) patients, the leak was resolved by primary therapy. Three patients underwent secondary therapy that included overlapping SEMS placement (in one patient), SEMS replacement (in one patient), and short plastic biliary stent placement with Argon plasma coagulation (APC) to create a raw surface and induce granulation tissue. The median duration for leak closure was 12 weeks (range: 8–24 weeks). One patient who had partial distal migration underwent overlapping SEMS placement. Three patients had nonbleeding ulcers at the distal end of SEMS at removal.Conclusion Endotherapy is effective and safe for the management of post-LSG leaks. Additional endotherapy can be used if primary therapy is not successful for resolution of the leak.
Keywords: obesity; laparoscopic sleeve gastrectomy; leaks; endoscopy; mega SEMS